cemas, karier eksplorasi kecemasan karier pada mahasiswa tingkat akhir di universitas mercu buana yogyakarta - noviyanti, arista (Universitas Muhammadiyah Magelang, 2022)
Arista Noviyanti. (2022). Exploration of Career Anxiety in Final Year Students at Mercu Buana University Yogyakarta. Thesis. Guidance and Counseling Study Program, Mercu Buana University Yogyakarta. This study aims to describe the feelings of career anxiety, dynamics of anxiety and efforts to overcome career anxiety in final year students at Mercu Buana University, Yogyakarta. This type of research uses descriptive qualitative. The research subjects consisted of 3 final year students at Mercu Buana University, Yogyakarta. The data collection method used is interview, observation and documentation. In this study, the researcher used incidental sampling technique. To measure the validity of the data, the researchers used source triangulation. The results of this study indicate that the subject experiences severe anxiety about a future career, the impact of this anxiety makes the subject often experience excessive anxiety such as a gloomy career picture, chaotic feelings, unable to regulate emotions properly and low self-confidence. The factors that influence the feeling of anxiety originate from the environment around the subject. Efforts made by the subject to reduce feelings of anxiety are by trying to think positively about future careers, seeking information about the world of work and trying to understand their abilities or potential.